'To Adopt or not to Adopt?' Legume Adoption in Maize‐Based Systems of Northern Thailand: Constraints and Potentials. (20th June 2016) - Yap, Von Yi; de Neergaard, Andreas; Bruun, Thilde Bech
Abstract: A considerable growth in the maize ( Zea mays L.) sector in Southeast Asia has resulted in a rapid expansion and intensification of maize monoculture on sloping uplands. This practice entailed the heavy use of fertilisers, leading to environmental degradation and farmers' indebtedness. Intercropping of legumes with maize could complement or replace fertiliser inputs; however legume adoption by smallholder maize farmers remains low. This study investigates the constraints and potentials to integrate legumes in maize‐based cropping systems in such environments. A comparative study between maize monocropping and maize/legume relay cropping was carried out in two villages of Thailand, using surveys, participatory rural appraisal (PRA) tools and interviews. The results demonstrated that both cropping systems were equally profitable, although the maize yield in maize/legume relay cropping was lower than that in monocropping. Low selling price was the most cited reason by the non‐adopters for not introducing legumes. Selling price of legume grains, ease of harvesting, marketability and ease of growing were the four main criteria that determined the adopters' choice of legume species. Among the cultivated legumes, ricebean ( Vigna umbellata L.) best fulfilled the criteria for the choice of legume species. Establishing maize/legume relay cropping as an alternative to maize monocropping under rainfed conditions can decrease risks, due to reduced expenses for farm inputs and similar economic returns. This study generated useful information for agricultural policy makers and development practitioners in identifying the barriers and facilitating factors that influence farmers' decision to adopt legumes and the conditions that shape the farmers' decision‐making environment. Copyright © 2016 John Wiley & Sons, Ltd.